IMPLEMENTASI PERDA NOMOR 3 TAHUN 2010 TENTANG PENANGGULANGAN HIV/AIDS DI KABUPATEN SEMARANG - Aji, Prajawan Galih Prasetya; Hidayat, Zainal; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2016)
This research while such the number of the HIV/AIDS in district Semarang are increasing. Lack of health facilities associated could have an impact on the to the reproductive age. The formulation problems this research include: how the implementation of those two years about 3 2010 HIV/AIDS in district Semarang? , what many factor are affecting the implementation of local regulations?. Research purposes to know the legislation number 3 years 2010 about HIV/AIDS in district Semarang. Research purposes to know the legislation number 3 years 2010 about HIV/AIDS in district Semarang. A literature study underlying this research using the theory George Edward III. The methodology used by the methodology qualitative .Analysis by using taxonomic analysis techniques and analysis of cultural theme . The result showed that the implementation of HIV/AIDS in district Semarang not optimally .This was apparent from the three phases which includes prevention , treatment , and rehabilitation. It is proven with increased rates of the HIV/AIDS , the number of health facilities inadequate to include the whole the district Semarang , and the availability of human resources not enough. Ineffective HIV/AIDS because the sectoral ego between government agencies and across the private sector , the stigma negative for the HIV/AIDS , and the culture permissiveness in society about. Based on the research done is recommended deprive sectoral ego happened , improve public education for HIV/AIDS , and improve health facilities and the quality of human resources.